2015
DOI: 10.1183/09031936.00097214
|View full text |Cite
|
Sign up to set email alerts
|

BioCAST/IFCT-1002: epidemiological and molecular features of lung cancer in never-smokers

Abstract: Lung cancer in never-smokers (LCINS) (fewer than 100 cigarettes in lifetime) is considered as a distinct entity and harbours an original molecular profile. However, the epidemiological and molecular features of LCINS in Europe remain poorly understood.All consecutive newly diagnosed LCINS patients were included in this prospective observational study by 75 participating centres during a 14-month period. Each patient completed a detailed questionnaire about risk factor exposure. Biomarker and pathological analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
62
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 28 publications
8
62
0
2
Order By: Relevance
“…Similar results have been found for exposure in the workplace and during childhood [4,5]. In a recent French study, we reported that 66% of LCINSs had been exposed to passive smoke, especially women and those exposed in domestic settings [6,7].…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…Similar results have been found for exposure in the workplace and during childhood [4,5]. In a recent French study, we reported that 66% of LCINSs had been exposed to passive smoke, especially women and those exposed in domestic settings [6,7].…”
Section: Introductionsupporting
confidence: 73%
“…Similar concerns may occur for the PSY variable. In addition, the population in which the studies were conducted differed from study to study, ranging from Asian only [13,14,16] to primarily Caucasian [7,15], and from never-smoker only [13,14] to all smoking statuses mixed [16]. These differences may also account for the conflicting results, as genomic susceptibility and confounding related to risk-factor exposure could differ depending on geographical origin [2,25].…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…BioCAST is a prospective, multicentric cohort sponsored by the French intergroup IFCT, designed to describe clinical, pathologic, and molecular epidemiology of LCINS in a French population. The detailed protocol is reported elsewhere (24). Briefly, newly diagnosed cases of NSCLC from self-declared nonsmokers were included and surveyed.…”
Section: Patientsmentioning
confidence: 99%
“…These rates were similar to the largest ever cohort of East Asian NSCLC never-smokers, reported by KIM et al [19], which observed 229 tumours; the frequency of EGFR mutations, ALK rearrangements, KRAS mutations and no mutations was 48%, 8.3%, 3.5%, and 40.2%, respectively. The gene modification frequencies reported by COURAUD et al [12] are slightly different from those seen in the Biomarker France study (preliminary results on 9911 NSCLC patients): EGFR (33%), KRAS (9.6%), BRAF (1.8%), PI3K (3.6%), HER2 (3.8%) mutations and ALK rearrangements (9.7%) in never-smokers (17.7% of the tested NSCLC patients) [20]. No mutations were reported in 35.2% of never-smokers in the Biomarker France study, compared to 27% in the present study.…”
mentioning
confidence: 92%